Isolation and Characterization of Lactic Acid Bacteria in Cincalok from Pengujan Village, Riau Islands - Oktavia, Yulia; Abiyyah, Ayu; Jumsurizal, Jumsurizal; Wulandari, Wulandari (Sriwijaya Journal of Environment, 2025)
Cincalok is a fermented food made from Acetes sp. The fermentation process requires the help of lactic acid bacteria. Lactic acid bacteria during the fermentation process function as antimicrobials, flavor enhancers, and extend food storage time. The research aimed to isolate and identify lactic acid bacteria contained in cincalok. Isolation was done to get a pure culture of bacteria grown on MRSA with the pour plate technique. The Morphological test was done to know the character of the colony and cell, and biochemical characterization was also done. The result of this study showed there are 5 isolates of bacteria have been isolated from Cincalok. The results of morphological and biochemical characterization showed that 5 isolates are lactic acid bacteria.